Members of the Jagged/Notch Gene Families Are Expressed in Injured Arteries and Regulate Cell Phenotype via Alterations in Cell Matrix and Cell-Cell Interaction - Lindner, Volkhard (American Society for Investigative Pathology, 2001)
The Jagged/Notch signaling pathways control cell fate determination and differentiation, and their dysfunction is associated with human pathologies involving cardiovascular abnormalities. To determine the presence of these genes during vascular response to injury, we analyzed expression of Jagged1, Jagged2, and Notch1 through 4 after balloon catheter denudation of the rat carotid artery. Although low levels of Jagged1, Jagged2, and constitutive expression of Notch1 were seen in uninjured endothelium, expression of all was significantly increased in injured vascular cells. High Jagged1 expression was restricted to the regenerating endothelial wound edge, whereas Notch transcripts were abundant in endothelial and smooth muscle cells. To understand the basis for Jagged/Notch control of cellular phenotype, we studied an in vitro model of NIH3T3 cells transfected with a secreted form of the extracellular domain of Jagged1. We report that the soluble Jagged1 protein caused decreased cell-matrix adhesion and cell migration defects. Cadherin-mediated intercellular junctions as well as focal adhesions were modified in soluble Jagged1 transfectants, demonstrating that cell-cell contacts and adhesion plaques may be targets of Jagged/Notch activity. We suggest that Jagged regulation of cell-cell and cell-matrix interactions may contribute to the control of cell migration in situations of tissue remodeling in vivo.